2020
DOI: 10.2478/sjecr-2018-0004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Burnout Syndrome and Anxiety in Military Personnel

Abstract: Professional military personnel are exposed to a large number of stressors every day at a higher rate than the civilian population, which can lead to psychological disturbances, primarily anxiety, as well as burnout syndrome. Th e aim of our investigation was to determine the correlation between burnout syndrome and anxiety in military personnel of the Serbian Armed Forces. Th e cross-sectional study included a total of 311 professional military personnel (officers, non-commissioned officers and professional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…Our findings are compatible with published studies that demonstrate an increased risk of burnout among women ( 23–25 , 36 , 46 ). In our study, the male sex of the employees also stood out as a significant variable for the higher PA subscale.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are compatible with published studies that demonstrate an increased risk of burnout among women ( 23–25 , 36 , 46 ). In our study, the male sex of the employees also stood out as a significant variable for the higher PA subscale.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are compatible with published studies that demonstrated an increased risk of job burnout with increased age. Results of a study performed on the professional military personnel of the Serbian Armed Forces ( 46 ) showed that the highest level of burnout was measured on the subscales EE in military personnel aged 23–30 years of age ( p < 0.05). De Solana reported that being younger contributed to increased burnout levels ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of a study performed in the professional military personnel of Serbian Armed Forces ( 28 ) showed that the highest level of burnout was measured on the subscales Emotional exhaustion (EE) in military personnel aged 23–30 years of age ( p < 0.05) and anxiety increased with age ( p < 0.001). Total scores on the subscales EE and DP increased, while on the subscale PA decreased with the increase of the total score of Back Anxiety Inventory Scale ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Later, others differentiated the stressors into four groups based on the sources of risk in this profession [12]: management, the performance of tasks, the community, and the judicial system. These effects of the stress and stressors are not exclusive to the police profession but are faced by other related professions such as the armed forces and, in general, all the state security forces and corps [3,[13][14][15][16][17]. This is also the case with death anxiety, which has been able to develop in overflowing situations very close to death and which could interfere with professional development since it is not possible to identify it at the time [18].…”
Section: Introductionmentioning
confidence: 99%